Plasma-wall interaction impact of the ITER re-baseline - R.A. Pitts; A. Loarte; T. Wauters; M. Dubrov; Y. Gribov; F. Köchl; A. Pshenov; Y. Zhang; J. Artola; X. Bonnin; L. Chen; M. Lehnen; et al. (Nuclear Materials and Energy)
To mitigate the impact of technical delays, provide a more rationalized approach to the safety demonstration and move forward as rapidly as possible to a reactor relevant materials choice, the ITER Organization embarked in 2023 on a significant re-baselining exercise. Central to this strategy is the elimination of beryllium (Be) first wall (FW) armour in favour of tungsten (W), placing plasma-wall interaction (PWI) centre stage of this new proposal. The switch to W comes with a modified Research Plan in which a first “Start of Research Operation” (SRO) campaign will use an inertially cooled, temporary FW, allowing experience to be gained with disruption mitigation without risking damage to the complex water-cooled panels to be installed for later DT operation. Conservative assessments of the W wall source, coupled with integrated modelling of W pedestal and core transport, demonstrate that the elimination of Be presents only a low risk to the achievement of the principal ITER Q = 10 DT burning plasma target. Primarily to reduce oxygen contamination in the limiter start-up phase, known to be a potential issue for current ramp-up on W surfaces, a conventional diborane-based glow discharge boronization system is included in the re-baseline. First-of-a-kind modelling of the boronization glow is used to provide the physics specification for this system. Erosion simulations accounting for the 3D wall geometry provide estimates both of the lifetime of boron (B) wall coatings and the subsequent B migration to remote areas, providing support to a simple evaluation which concludes that boronization, if it were to be used frequently, would dominate fuel retention in an all-W ITER. Boundary plasma (SOLPS-ITER) and integrated core–edge (JINTRAC) simulations, including W erosion and transport, clearly indicate the tendency for a self-regulating W sputter source in limiter configurations and highlight the importance of on-axis electron cyclotron power deposition to prevent W core accumulation in the early current ramp phase. These predicted trends are found experimentally in dedicated W limiter start-up experiments on the EAST tokamak. The SOLPS-ITER runs are used to formulate W source boundary conditions for 1.5D DINA code scenario design simulations which demonstrate that flattop durations of ∼100 s should be possible in hydrogen L-modes at nominal field and current (Ip = 15 MA, BT = 5.3 T) which are one of the principal SRO targets. Runaway electrons (RE) are considered to be a key threat to the integrity of the final, actively cooled FW panels. New simulations of RE deposition and subsequent thermal transport in W under conservative assumptions for the impact energy and spatial distribution, conclude that there is a strong argument to increase the W armour thickness in key FW areas to improve margins against cooling channel interface damage in the early DT operation phases when new RE seeds will be experienced for the first time.